Improving the Lifetime of CsPbBr3 Perovskite in Water Using Self-Healing and Transparent Elastic Polymer Matrix - Laysandra, Livy; Fan, Yong Jie; Adena, Cecilia; Lee, Yen-Ting; Au-Duong, Ai-Nhan; Chen, Liang-Yih; Chiu, Yu-Cheng (Frontiers in Chemistry, 2020)
Here, we develop a simple and efficient strategy to stabilize inorganic halide perovskite CsPbX3 at high relative humidity by embedding it into the matrix with elastic and self-healing features. The polymer matrix, owning naturally hydrophobic characteristic of butyl acrylate (BA) and cross-linkable and healable moiety from N-(hydroxymethyl)acrylamide (NMA), was chosen as providing not only a surrounding protective layer for inorganic perovskite but also the stretching, and healing properties to the whole the organic-inorganic hybrid composite. This fabricated hybrid composite was demonstrated to stably persist against the suffering from hydrolysis of perovskites when exposed to high moisture surrounding. The relative PL intensity of hybrid composites after crosslinking was found relatively stable in air after 5 days exposure. Upon water immersion, the PL intensity of hybrid composite was only shown a decrease of 32% after the first 6 hours, then remaining stable in the next 6 hours afterward. Furthermore, this fabricated hybrid composites is not only flexible, stretchable and relatively transparent but also exhibits excellent self-healing capability in environmental condition (T = 25C), in which the self-healing efficiency for 24 hours is above 40%. The tensile strength and stretching ability of 5 wt% perovskite content in the random copolymer (hybrid composites) were observed to be 3.8 MPa and 553.5% respectively. Overall, stretchable and autonomous self-healing properties combining with highly luminescent characteristics are very promising materials for next-generation soft optical devices.